Efficacy and Safety of Adherence to dl-3-n-Butylphthalide Treatment in Patients With Non-disabling Minor Stroke and TIA—Analysis From a Nationwide, Multicenter Registry - Tan, Zefeng; Zhao, Yin; Yang, Wanyong; He, Shenwen; Ding, Yan; Xu, Anding (Frontiers in Neurology, 2021)
Background: Dl-3-n-Butylphthalide (NBP) has the potential to improve clinical outcomes in acute ischemic stroke patients by improving collateral circulation. We aimed to evaluate the efficacy and safety of NBP in patients with non-disabling minor ischemic stroke and transient ischemic attack (TIA). Methods: The BRIDGE (the observation study on clinical effectiveness of NBP on patients with non-disabling ischemic cerebrovascular disease) is a prospective registry to monitor the efficacy and safety of NBP therapy in acute non-disabling ischemic stroke or high-risk TIA. Non-disabling minor ischemic stroke patients within 48 h were enrolled across 51 stroke centers in China. We divided patients into NBP compliance or non-compliance groups according to their adherence to NBP. The primary outcome was the favorable functional outcome at 90 days, defined as a modified Rankin scale (mRS) <2. Results: Between 10th October 2016 and 25th June 2019, 3,118 patients were included in this analysis. In multivariable analysis, after adjusting for common risk factors and demographic factors, NBP-compliance group has a higher proportion of favorable functional outcome (92.1 vs. 87.4%, adjusted odds ratio 2.00, 95% confidence interval, 1.50–2.65), and a higher stroke recurrence rate (2.40 vs. 0.31%, adjusted odds ratio 8.86, 95% confidence interval, 3.37–23.30) than the NBP-non-compliance group. There was no significant difference in death and intracranial hemorrhage rate between the two groups. In subgroup analysis, patients with National Institutes of Health Stroke Scale (NIHSS) scores from 3 to 5 who complied to NBP therapy had a higher rate of favorable functional outcomes than the NBP-non-compliance group. [88.82 vs. 76.21%, adjusted odds ratio 2.52 (1.81–3.50), adjusted interaction P = 0.00]. Conclusion: In non-disabling minor ischemic stroke or TIA patients, compliance with NBP therapy led to better 90-day functional outcomes despite a higher risk of recurrence, and this effect seems to be stronger in patients with NIHSS scores of 3–5. Further large randomized, double-blind controlled studies to analyse the association between NBP and functional outcome is warranted in the coming future.